Hubungan Depresi dengan Kemampuan Dalam Aktivitas Dasar Sehari-Hari Pada Lanjut Usia di Panti Sosial Tresna Werdha Minaula Kendari - Dimas Aji Pamungkas; Tomy Nurtamin; Junuda Junuda (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2016)
According to PPDGJ-III depression is a mental disorder that has three major symptoms of depressive affect, loss of interest and easily tired state, and has seven other symptoms such as reduced concentration, reduced confidence, feelng of guilty, pessimistic, suicidal ideas, sleep disturbance and loss of appetite. These problem could be acute or chronic and lead impaired ability of individuals in everyday activities. Activity Daily Living is work activities of daily routine. Activity Daily Living is a staple for self-care activities. These study aims to determine the relationship between depression and activity daily living the elderly in Panti Sosial Tresna Werdha “Minaula” Kendari. These study was an observational analytic study with cross sectional design. The population from  elderly in Panti Sosial Tresna Werdha "Minaula" Kendari. Sample in these study consist of  95 respondent. Elderly male cosist of 35 respondents and female 36 respondents. The sampling method is total sampling. The study instrument used questionnaires Beck Depression Inventory (BDI) to assess depression in the elderly. Assessment Activity Daily Living (ADL) using the Barthel Index questionnaire. Data were analyzed by Spearman test. Data was cosidered significant at p value ≤ 0,05. The Results of these study  that 71 respondents was mild depression (43.7%), no depression (33.8%) and moderate depression (22.5%).  The Respondent who can perform the Activity Daily Living consist of independently (42.3%), mild dependence (38.0%), moderate dependence (9.9%), heavy dependence (7.0%) and total dependence (2.8%). There were a significant relationship between depression on Activity Daily Living (p = 0.000) with negative correlation direction or opposite direction (r = -0.500). The conclusions of these study indicate that there were relationship of depression of activity daily living the elderly in Panti Sosial Tresna Werdha “Minaula” Kendari.Keywords: Activity Daily Living, Depression, Elderly